2020
DOI: 10.1111/odi.13303
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms and recurrent aphthous stomatitis—Evidence from a population‐based study in Indonesia

Abstract: Objectives This study aims to report the prevalence and distribution of recurrent aphthous stomatitis (RAS) among Indonesian adults and to test the relationship between symptom of depression and RAS. Methods Data from the 2007 Indonesia Family Life Survey (IFLS 2007) were analysed to assess the association between symptom of depression and RAS. The prevalence of RAS in the previous month was self‐reported. Symptom of depression was measured using the 10‐item Center for Epidemiologic Studies Depression (CES‐D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
14
1
2
Order By: Relevance
“…In this systematic review, we evaluated the therapeutic effects of medicinal plants on recurrent aphthous lesions based on the extant evidence from randomized controlled trials. Various causative factors may play role in the development of RAS, including microbial, hormonal, nutritional, immunological, and psychological factors (Belenguer‐Guallar et al, 2014; Gallo et al, 2009; Hariyani, Bramantoro, Nair, Singh, & Sengupta, 2020; Stehlikova et al, 2019), and trauma (Jurge et al, 2006) (Figure 2). Although there is no definite cause for RAS, previous studies have extensively focused on immunological factors (Akintoye & Greenberg, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, we evaluated the therapeutic effects of medicinal plants on recurrent aphthous lesions based on the extant evidence from randomized controlled trials. Various causative factors may play role in the development of RAS, including microbial, hormonal, nutritional, immunological, and psychological factors (Belenguer‐Guallar et al, 2014; Gallo et al, 2009; Hariyani, Bramantoro, Nair, Singh, & Sengupta, 2020; Stehlikova et al, 2019), and trauma (Jurge et al, 2006) (Figure 2). Although there is no definite cause for RAS, previous studies have extensively focused on immunological factors (Akintoye & Greenberg, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There might be three combined factors for the increased RAS in doctor/nurse population. First, recent researches indicate the doctor and nurse as one of the population with greatest professional pressure suffers from more distress [ 26 ] and RAS is associated with psychological factors [ 2 , 3 , 6 ]. Long-term follow up study from university to career also found the RAS prevalence rate is relatively high in the doctor/nurse and dental profession [ 2 , 7 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gejala depresi memiliki keterkaitan dengan prevalensi sariawan dikarenakan stress maupun depresi memicu abnormalitas mekanisme stomatognatik, sehingga menyebabkan trauma pada permukaan mukosa rongga mulut dan menimbulkan ulserasi (5) . Namun dalam sebuah penelitian yang meneliti hubungan antara kejadian sariawan dan keadaan psikologis mengungkapkan bahwa depresi dan gangguan psikologis yang lain merupakan dampak dari sariawan (19) .…”
Section: Hubungan Gejala Depresi Dengan Kejadian Sariawanunclassified